2022
DOI: 10.1097/prs.0000000000009143
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Differences in Sagittal Synostosis with Age before Surgery

Abstract: agittal synostosis presenting with scaphocephaly is the most common form of craniosynostosis. 1 Various phenotypes have been described, including frontal bossing, occipital protuberance, bitemporal protrusion, and coronal constriction, 2 in addition to variations in treatment with regard to timing 3,4 and technique. 5-8 However, a commonality is to achieve an increase in parietal width and a decrease the cephalic index, as a measure of cranial length to width. 9 There are several considerations that go into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…37 Patients presenting to our center at younger ages presented with more severe scaphocephaly and increased relative posterior vault volume suggesting occipital protuberance; children presenting at older ages presented with more severe middle vault constriction. 3 When assessing for predictors of long-term morphometric outcomes in SS, we found that preoperative severity was the best predictor across all measurements. Performing open middle and posterior cranial vault expansion at older ages was associated with longer skulls and higher posterior cranial vault volumes.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…37 Patients presenting to our center at younger ages presented with more severe scaphocephaly and increased relative posterior vault volume suggesting occipital protuberance; children presenting at older ages presented with more severe middle vault constriction. 3 When assessing for predictors of long-term morphometric outcomes in SS, we found that preoperative severity was the best predictor across all measurements. Performing open middle and posterior cranial vault expansion at older ages was associated with longer skulls and higher posterior cranial vault volumes.…”
Section: Discussionmentioning
confidence: 83%
“…31 In addition to cephalic index differences, SS results in frontal bossing, midline occipital protuberance, and biparietal narrowing. 3 The anthropometric study by Fearon et al 25 also noted that there was a reduction in frontal bossing as measured by the minimal frontal breadth, without any direct surgical manipulation of the anterior cranium. This is consistent with our previous study suggesting the forehead dysmorphology of SS improves without an anterior cranial surgery, reporting normalization of the horizontal bossing ratio, vertical bossing ratio, and the frontal bossing angle 2 years after middle and posterior vault cranial expansion.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations